STMO-13 PATHOLOGICAL EVALUATION AND ONCOLOGICAL OUTCOME OF FLAIRECTOMY IN PATIENTS WITH IDH1 WILD-TYPE GLIOBLASTOMA. (3rd December 2022) - Hirono, Seiichiro; Kouchi, Yusuke; Kishimoto, Takashi; Kobayashi, Masayoshi; Matsutani, Tomoo; Iwadate, Yasuo
Abstract: Purpose: The pathological significance as well as oncological outcome of FLAIRectomy in patients with IDH1 wild-type Glioblastoma are unknown. Methods: We conducted a retrospective review in newly-diagnosed, IDH1 wild-type glioblastoma who achieved gross total resection (GTR) of enhancing tumor. Pre- and post-operative volume of FLAIR abnormal area were also calculated. All patients underwent standard radiotherapy and temozolomide treatment, and monitored for tumor recurrence and overall survival (OS). Results: A total of 25 GTR patients were included in the study, and the median FLAIRectomy and residual FLAIR volume were 51.5% and 19.6cc respectively. More than 80% of GTR patients unintentionally achieved 20% and more of FLAIRectomy. The pathological specimen of FLAIR abnormal area without gadolinium enhancement was obtained in 6 out of 25, and the typical features of GBM was found in only one. Following FLAIRectomy >20%, majority of recurrence was local. The progression-free and overall survival of those 25 patients were 14.9 months and 30.5 months respectively. Conclusion: Although this study confirmed the unintentional FLAIRectomy >20% in most of GTR patients, the improvement of local control and survival was not clarified, necessitating prospective study with pathological and neurofunctional evaluation.